An in vitro evaluation of microleakage in class V cavities restored with silorane-based resin composite using different adhesive systems - Fonseca, Beatriz Maria da; Dias, Kátia Regina Hostilio Cervantes; Ferreira, Juliane Otoni dos Reis; Silva, Isabela Rocha da; Rabello, Tiago Braga (Brazilian Dental Science, 2012)
.